Vocabulary Mastery Is Not Everything: The Impact of Reading Habits on Popular Scientific Article Writing Skills - Kurniawati, Heni; Suroso, Eko (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Popular scientific articles require not only linguistic accuracy but also the ability to adapt style and structure for a broad audience. This study examines the association between vocabulary mastery and the quality of popular scientific article writing, and describes learner profiles related to reading exposure to popular science texts among junior high school students. Using a quantitative correlational design, data were collected from one Grade VIII class at SMP Negeri 5 Cilacap (AY 2024/2025) selected through purposive sampling. Instruments included a multiple-choice vocabulary test and a writing task assessed with an analytic rubric covering Creativity & Engagement, Structure & Organization, and Vocabulary & Sentence Variety. Because one variable was non-normally distributed, Spearman’s rho was applied, complemented by scatter/box-plot visualizations and quadrant mapping to profile outliers and compensation patterns. Results showed a weak, positive, and non-significant correlation between vocabulary mastery and writing quality (ρ = 0.233; p = 0.199). Visualization revealed heterogeneous profiles: some students with limited vocabulary achieved adequate writing through organization and rhetorical strategies (Low-High quadrant), while some with higher vocabulary underperformed when structure and audience adaptation were weak (High-Low quadrant). Groups with higher reading exposure to popular science tended to obtain consistently higher rubric scores. For that, vocabulary supports writing, but it is not a sufficient determinant of success in popular science writing. Instruction should integrate vocabulary development, regular reading of popular science texts, and explicit teaching of rhetorical organization and audience adaptation.